GAMBARAN POLA PENGGUNAAN ANTIBIOTIKA PADA PASIEN PNEUMONIA DI PUSKESMAS S PERIODE JANUARI – DESEMBER 2023 - rahayu, sri; Assifatun Nisa; Soraya (Akademi Farmasi Yarsi Pontianak, 2024)
Pneumonia is an inflammation of the lungs which causes pain when breathing and limited oxygen intake. There are various ways in which pneumonia can be spread, including coughing and sneezing. According to data from Risksdas, there has been an increase in the prevalence of pneumonia at all ages from 2.1% in 2007 to 2.7% in 2013 and 4.5% in 2018. Antibiotics are in 6th place, including the 10th most commonly used drugs in Puskesmas S in 2022. This research aims to gain insight into the pattern of antibiotic use in pneumonia patients at the S Community Health Center for the period January-December 2023. This research is a descriptive study that retrospectively analyzes data using a purposive sampling technique to obtain a sample of 232 prescriptions. The results indicated that amoxicillin was the most commonly prescribed antibiotic, with 186 prescriptions (80.17% of the total). Cefixime was the second most commonly prescribed antibiotic, with 24 prescriptions (10.34% of the total). Cefadroxil was the third most commonly prescribed antibiotic, with 22 prescriptions (9.49% of the total). It is worth noting that pneumonia attacks children aged 0-5 years as many as 98 patients with a percentage of (42.24%), and adults aged 46-55 years with a percentage of 14 patients with a percentage of (6.04%). It would also be beneficial to consider the gender of the patients, with males being more susceptible than females. It is worth noting that men were more likely to suffer from pneumonia, with 134 patients (57.76%) affected. The drug class that was most widely used was the penicillin drug group, with 186 prescriptions (80.18%).